Local Uniform Strong Proximinality of the Space of Continuous Vector-Valued Functions. (3rd August 2017) - Indumathi, V.; Prakash, N.
ABSTRACT: Let X be a Banach space, S be a compact Hausdorff space and Y be a U-proximinal subspace of X . We prove that C ( S, Y ) is locally uniformly strongly proximinal in C ( S, X ) and the corresponding metric projection map is Hausdorff metric continuous.